Development of an electrocardiogram-based risk calculator for a cardiac cause of syncope. Issue 22 (27th January 2021) - Zimmermann, Tobias; du Fay de Lavallaz, Jeanne; Walter, Joan Elias; Strebel, Ivo; Nestelberger, Thomas; Joray, Lydia; Badertscher, Patrick; Flores, Dayana; Widmer, Velina; Geigy, Nicolas; Miro, Oscar; Salgado, Emilio; et al.
Abstract : Objective: To develop an ECG-based tool for rapid risk assessment of a cardiac cause of syncope in patients ≥40 years. Methods: In a prospective international multicentre study, 2007 patients ≥40 years presenting with syncope were recruited in the emergency department (ED) of participating centres ranging from large university hospitals to smaller rural hospitals in eight countries from May 2010 to July 2017. 12-Lead ECG recordings were obtained at ED presentation following the syncopal event. The primary diagnostic outcome, a cardiac cause of syncope, was centrally adjudicated by two independent cardiologists using all available clinical information including 12-month follow-up. ECG predictors for a cardiac cause of syncope were identified using penalised backward selection and a continuous-scale likelihood was calculated based on regression analysis coefficients. Findings were validated in an independent US multicentre cohort including 2269 patients. Results: In the derivation cohort, a cardiac cause of syncope was adjudicated in 267 patients (16%). Seven ECG criteria were identified as predictors for this outcome: heart rate and QTc-interval (continuous predictors), rhythm, atrioventricular block, ST-segment depression, bundle branch block and ventricular extrasystole/non-sustained ventricular tachycardia (categorical predictors). Diagnostic accuracy of these combined predictors for a cardiac cause of syncope was high (area under the curve 0.80, 95% CI 0.77 to 0.83). Overall, 138 patients (8%) were rapidly triaged towards rule-out and 181 patients (11%) towards rule-in of a cardiac cause of syncope. External validation showed similar performance. Conclusion: In patients ≥40 years with a syncopal event, a combination of seven ECG criteria enabled rapid assessment of the likelihood that syncope was due to a cardiac cause. Trial registration number: NCT01548352 (BASEL IX), NCT01802398 (SRS study).